2014
DOI: 10.1287/orsc.2014.0909
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence in Organizations: A Multilevel Approach

Abstract: T he experience of simultaneously positive and negative orientations toward a person, goal, task, idea, and such appears to be quite common in organizations, but it is poorly understood. We develop a multilevel perspective on ambivalence in organizations that demonstrates how this phenomenon is integral to certain cognitive and emotional processes and important outcomes. Specifically, we discuss the organizational triggers of ambivalence and the cognitive and emotional mechanisms through which ambivalence diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
427
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(449 citation statements)
references
References 160 publications
13
427
1
8
Order By: Relevance
“…Our insights and measures can apply to these and other streams of research that focus on different reactions to conflicts and tensions in organizational and team contexts. Considering individual variance in paradox mindset can also help differentiate between positive and negative consequences of experiencing and expressing ambivalence (Ashforth, Rogers, Pratt, & Pradies, 2014;Rothman & Melwani, 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Our insights and measures can apply to these and other streams of research that focus on different reactions to conflicts and tensions in organizational and team contexts. Considering individual variance in paradox mindset can also help differentiate between positive and negative consequences of experiencing and expressing ambivalence (Ashforth, Rogers, Pratt, & Pradies, 2014;Rothman & Melwani, 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Despite the persistent nature of paradoxes, studies relatively often examine specific consequences of paradox and its (mis)management, as seen in 48 of the analyzed studies (36%). On the negative side, studies found that defensive individual or collective responses, pulling toward one extreme or avoiding engagement with paradox, can have undesired consequences (Bartunek, Walsh, & Lacey, 2000), fostering ambivalence (Ashforth, Rogers, Pratt, & Pradies, 2014), and causing chaos (Thiétart & Forgues, 1995). If not managed effectively, paradoxical forces can neutralize each other's beneficial side or spark conflict .…”
Section: --------------------------------mentioning
confidence: 99%
“…Dissonance theory (Festinger, 1957) posits that holding two inconsistent thoughts at the same time is experienced as aversive. Ambivalence is considered by some to be a more intense form of cognitive dissonance, since the competing attitudes are derived from opposite extremes (Baek 2010;Ashforth et al, 2014).…”
Section: Theory and Background Of Hypothesesmentioning
confidence: 99%
“…The majority of this research examines positive and negative relationships independent of each other and neglects that sometimes organizational relationships are neither exclusively positive or negative, but both (Ashforth et al, 2014;Kreiner & Ashforth, 2004). An employee may have a relationship with their supervisor that vacillates between positive and negative experiences (e.g., being commended for good work and yelled at for something else).…”
mentioning
confidence: 99%
See 1 more Smart Citation